Importance of Non-research Articles in Scientific Publications of Health - Ackah, David; Ackah, Makafin R.A. (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Nowadays scientific publications online through electronic journals are becoming increasingly widespread. Many recent findings have been published through this system so that they can be deployed quickly, so that they can be used immediately by those who need them. Most of the articles that have been published in the form of research articles. This type of article is a summary of research reports conducted by researchers with the intention of getting spread widely so that it can be a reference for other researchers in their research activities, or applicable directly to those who need it. On the other hand, there are also types of non-research articles that are not less useful value such as opinion articles and correspondence. The opinion articles contain opinions about certain phenomena that can lead to ideas for further study, whereas correspondence articles contain responses to published articles.